Assessment of the dual role of Lyonia ovalifolia (Wall.) Drude in inhibiting AGEs and enhancing GLUT4 translocation through LC-ESI-QTOF-MS/MS determination and in silico studies - Sahu, Neha; Singh, Nitesh; Arya, Kamal Ram; Reddy, Sabbu Sathish; Rai, Amit Kumar; Shukla, Vijaya; Pandey, Jyotsana; Narender, Tadigoppula; Tamrakar, Akhilesh Kumar; Kumar, Brijesh; Rajak, Bikash Kumar; Malik, Sumira; et al. (Frontiers in Pharmacology, 2023)
Diabetes mellitus (DM) is a metabolic disorder which results in glucose accumulation in the blood accompanied by production of advanced glycation end products(AGEs)through glycation of cellular proteins. These AGEs interfere with insulin signalling and prevent GLUT-4 membrane translocation thereby promoting accumulation of more glucose in the blood and cause post-diabetic complications. In this paper we have examined the anti- diabetic potential of Lyonia ovalifolia (Wall.) Drude, a well-known ethnomedicinal plant of Indian Himalaya. Considering its several medicinal properties, its ethanolic extract and different solvent fractions were analysed for in-vitro anti-glycation activity and antidiabetic potential i.e. stimulation of GLUT-4 translocation. The results showed that extract and fraction showed increased antiglycation activity and an increased level of GLUT-4 translocation. Further 12 bioactive compounds of ethanolic extract identified through LC- ESI-QTOF-MS/MS analysis revealed the presence of three new compound Leucothol B, Rhodoterpenoids A, Leucothol A. Further molecular docking were done of identified compounds against key proteins of diabetes mellitus which includes Sirtuin family of NAD(+)-dependent protein deacetylases 6 (SIRT6), Aldose reductase (AR) and Tyrosine kinase (TK). In results we observed that luteolin revealed the best binding affinity (-12.3 kcal/mol) followed by eriodictyol, astilbin and syringaresinol. The ADMET study showed that luteolin, eriodictyol, astilbin and syringaresinol may be the promising drug candidate without any harmful effect following all the drug-likeness guidelines. Therefore, this study reveals for the first time that L. ovalifolia plays an important role in insulin homeostasis as shown by in vitro and in silico studies.